Carcinogenic effect of human tumor-derived cell-free filtrates in nude mice - Berlanga-Acosta, Jorge; Arteaga-Hernandez, Ernesto; Garcia-Ojalvo, Ariana; Duvergel-Calderin, Dayanis; Rodriguez-Touseiro, Marisol; Lopez-Marin, Laura; Suarez-Alba, Jose; Fuentes-Morales, Dasha; Mendoza-Fuentes, Osmany; Fernández-Puentes, Sheyla; Nuñez-Figueredo, Yanier; Guillen-Nieto, Gerardo (Frontiers in Molecular Biosciences, 2024)
Cancer remains a worldwide cause of morbidity and mortality. Investigational research efforts have included the administration of tumor-derived extracts to healthy animals. Having previously demonstrated that the administration of non-transmissible, human cancer-derived homogenates induced malignant tumors in mice, here, we examined the consequences of administering 50 or 100 µg of protein of crude homogenates from mammary carcinoma, pancreatic adenocarcinoma, and melanoma samples in 6 inoculations per week during 2 months. The concurrent control mice received homogenates of healthy donor-skin cosmetic surgery fragments. Mammary carcinoma homogenate administration did not provoke the deterioration or mortality of the animals. Multiple foci of lung adenocarcinomas with a broad expression of malignity histomarkers coexisting with small cell-like carcinomas were found. Disseminated cells, positive to classic epithelial markers, were detected in lymphoid nodes. The administration of pancreatic tumor and melanoma homogenates progressively deteriorated animal health. Pancreatic tumor induced poorly differentiated lung adenocarcinomas and pancreatic islet hyperplasia. Melanoma affected lungs with solid pseudopapillary adenocarcinomas. Giant atypical hepatocytes were also observed. The kidney exhibited dispersed foci of neoplastic cells within a desmoplastic matrix. Nuclear overlapping with hyperchromatic nuclei, mitotic figures, and prominent nuclear atypia was identified in epidermal cells. None of these changes were ever detected in the control mice. Furthermore, the incubation of zebrafish embryos with breast tumor homogenates induced the expression of c-Myc and HER-2 as tumor markers, contrasting to embryos exposed to healthy tissue-derived material. This study confirms and extends our hypothesis that tumor homogenates contain and may act as vectors for “malignancy drivers,” which ultimately implement a carcinogenesis process in otherwise healthy mice.